Propuesta para la implementación de un software para uso administrativo, presupuestal y contable de la personería del municipio de Tierralta (2022)
This work highlights the functions of the municipal office as a public entity and which are of utmost importance in the defense of the rights and the restitution of their rights to the most violated, as well as we will also find the operation, management and control in each of the areas that compose it, from the administrative and budgetary, to the legal area and how each of these areas are working manually, without any control and security in the information. All this was achieved through the application of various methods that allowed a deep analysis of the information obtained, which allowed to make a proposal for improvement for the entity, taking into account the guidelines to which public entities are subject.